2005
DOI: 10.1672/0277-5212(2005)025[0520:acaoss]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A comparative assessment of seedling survival and biomass accumulation for fourteen wetland plant species grown under minor water-depth differences

Abstract: The purpose of this experiment was to investigate the survival and biomass accumulation of wetland plant species under different water depths in controlled microcosms. In the greenhouse, two-weekold seedlings were randomly assigned to one of seven water-depth treatments (Ϫ6, Ϫ4, Ϫ2, 0, ϩ2, ϩ4, and ϩ6 cm relative to the soil surface) and allowed to grow for six months. Species included five perennial sedges, four perennial and one annual grasses, and two perennial and two annual forbs. Twelve of the species had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 48 publications
3
34
1
Order By: Relevance
“…The 475-ml cup was 14 cm in height; therefore the distances of water level to the bottom of the cup were 8, 10, 12, 14 and 16 cm from lowest to highest water depth. Fraser and Karnezis (2005) found that the percent of plant survivorship of five of the eight species at water depths greater than 2 cm above the soil surface was zero, and therefore water depth treatments above 2 cm were not included in the experiment reported here. Eight species tested across five water levels, plus five replicates, resulted in a total of 200 pots.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 475-ml cup was 14 cm in height; therefore the distances of water level to the bottom of the cup were 8, 10, 12, 14 and 16 cm from lowest to highest water depth. Fraser and Karnezis (2005) found that the percent of plant survivorship of five of the eight species at water depths greater than 2 cm above the soil surface was zero, and therefore water depth treatments above 2 cm were not included in the experiment reported here. Eight species tested across five water levels, plus five replicates, resulted in a total of 200 pots.…”
Section: Methodsmentioning
confidence: 99%
“…The other two species, P. arundinacea and Lythrum salicaria, were selected because they are also commonly found growing in the same freshwater marshes as the six native species but are non-native invasives (Apfelbaum andSams 1987, Thompson et al 1987). These eight species were also used in a previous study to measure the effects of minor water depth on biomass accumulation and survivorship (Fraser and Karnezis 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, there is still a wide range of growth response between wetland plant species to flooding and to tolerance of different water levels (Fraser and Karnezis 2005;Mitsch and Gosselink 2007;Araya et al 2010). One aspect of hydrology that is rarely considered in wetland plant studies is the indirect effects of hydrology on water chemistry.…”
Section: Management Implicationsmentioning
confidence: 99%
“…The seedling establishment phase of the life cycle is crucial to successful propagation of any plant. Notably, the water level is the most important factor affecting seedling survival and the establishment of submerged plants (Nicol and Ganf 2000, Fraser and Karnezis, 2005, Kwon et al 2007). Water level determines wetland plant community composition and zonation because of different response and adaptation of species (Casanova and Brock 2000).…”
Section: Introductionmentioning
confidence: 99%